Singapore : Detailed Assessment of Observance-Insurance Core Principles. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses findings of the Detailed Assessment of Observance on Insurance Core Principles on Singapore. The insurance industry in Singapore is growing, in particular the offshore nonlife sector. Gross premium of the sector has grown significantly by more than 80 percent in the last five years. The Monetary Authority of Singapore has made significant progress in improving the insurance regulatory regime and supervisory practice since the initial Financial Sector Assessment Program in 2004.The updated regulatory framework and supervisory practices have a significantly high level of observance of the Insurance Core Principles.